The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s13104-018-3806-7
|View full text |Cite
|
Sign up to set email alerts
|

Time to death and risk factors among tuberculosis patients in Northern Ethiopia

Abstract: ObjectiveThe main objective of this study was to assess time to death and associated risk factors among tuberculosis (TB) patients.ResultsA total of 769 TB patients were studied and of those, 87 (11.3%) patients died. All of the deaths occurred within 7 months of anti-tuberculosis therapy. Extra-pulmonary TB (AHR = 17.376, 95% CI; 3.88–77.86, p < 0.001) as compared to pulmonary TB and cotrimoxazole prophylaxis therapy (CPT) (AHR = 0.15, 95% CI; 0.03–0.74, p = 0.02) were found to be the predictors of mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
3
17
3
Order By: Relevance
“…In order to achieve the 2025 global milestone for reductions in TB deaths, a CFR of 6% or less is required by all NTPs [2]. The 13% overall CFR estimated in this present study compares favourably with what a previous South African study found (16.3%) in a 10-year electronic record review [33] and in Zimbabwe (22%) [34] but higher than findings reported in Ethiopia [35,36], Cape Town (3.7%) [37], Washington state, US (12.1%) [38] and Taiwan (12.3%) [39]. The differences in CFR in different settings might be due to the differences in the study sites, study period, the study design, and target population.…”
Section: Trends and Predictors Of Tb Mortalitysupporting
confidence: 46%
See 1 more Smart Citation
“…In order to achieve the 2025 global milestone for reductions in TB deaths, a CFR of 6% or less is required by all NTPs [2]. The 13% overall CFR estimated in this present study compares favourably with what a previous South African study found (16.3%) in a 10-year electronic record review [33] and in Zimbabwe (22%) [34] but higher than findings reported in Ethiopia [35,36], Cape Town (3.7%) [37], Washington state, US (12.1%) [38] and Taiwan (12.3%) [39]. The differences in CFR in different settings might be due to the differences in the study sites, study period, the study design, and target population.…”
Section: Trends and Predictors Of Tb Mortalitysupporting
confidence: 46%
“…[44,45]. Studies from different populations [35,46,47] have also shown that TB/HIV co-infected patients who were not taking CPT were at highest risk of death. This study, however, did not have the data to confirm or refute this claim.…”
Section: Trends and Predictors Of Tb Mortalitymentioning
confidence: 99%
“…However, the relevant departments cannot relax their vigilance and further measures are needed to strengthen the tracking, follow-up, and management of male, elderly, HIV-positive, retreated, and smear-positive TB patients, to further improve the treatment success rate. Focusing on adverse reactions and complications in administering antituberculosis treatment at an early stage will help improve the antiviral treatment effect and reduce the mortality rate [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct involvement of different risk factors for this dilemma are the distinct reason of increasing infection susceptibility, and PTB progression 15,16. These factors also play vital role in prediction of mortality in PTB patients, such as increasing age, poor health care facilities due to poverty, low income, anemia, CLD, DM, HIV, HTN, recurrent TB, and smoking 17,18…”
Section: Discussionmentioning
confidence: 99%